Leisure centre entrance charges and physical activity participation in England. (11th December 2017) - Ward, F; Halliday, E C; Barr, B; Higgerson, J; Holt, V
Summary: Reducing or eliminating the cost to the public of using leisure facilities is one tool that local authorities have available to reduce inequalities in physical activity (PA). There is limited evidence about the effect of leisure entrance charges and their impact on participation. This study aimed to ascertain how facility pricing influenced the decisions people made about how to pay and what to pay for and how, in turn, these decisions impacted on participation for different groups. A total of 83 members of the public living in 4 local authorities in the North West of England were involved in focus groups or individual interviews. The results show that cost was a key factor which influenced PA participation in low income neighbourhoods. In practise, however, the majority of service users navigated the range of prices or payment options to find one that was suitable rather than simply reporting whether leisure was affordable or not. Whilst pre-paid options (e.g. direct debit memberships) encouraged participation, entrance charges incurred each time an individual participated had a negative impact on frequency but were a convenient way of paying for occasional use or for people who were unable to afford a pre-paid option. Free access also helped people who could not afford pre-paid membership to exercise regularly as well as incentivizing non-users to try activities. The research concluded that policies that include components of free access and offer more flexible payment options are most likely to contribute to reducing inequalities in PA.